Meningkatkan Keterampilan Penggunaan Teknologi di Bidang Pendidikan dan Ekonomi melalui Program Desa Terampil - Awi Dassa; Hisyam Ihsan; Muhammad Ammar Naufal; Ruslan; Andi Ammar Akrar (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Desa Terampil program is an implementation of the awareness about the importance of mastering skills in using technology, especially in the fields of education and economy. This program was implemented by the KKN Tematik Team of the Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar in two places, which are SMK Negeri 3 Bone and SMP Negeri 1 Libureng. The main objectives of this program are to improve the ability of teachers to use Canva in making learning media and disseminating information about the QRIS digital payment system. The results obtained are that teachers can use Canva in making learning media and students and teachers recognize and can use QRIS in transactions.